Dynamic interference avoidance of 2-DOF robot arms using interval analysis - Fang, H.; Merlet, J.-P. (2005 IEEE/RSJ International Conference on Intelligent Robots and Systems, 2005)
In this paper the problem of interference avoidance for robots subject to dynamic constraints is investigated. First computed-torque method is used to obtain a linearized closed-loop system. For this linearized system the desired state that the robot is going to take at the next sampling period is checked by phase plane analysis to ensure the robot can be stopped without interferences, dynamic constraints are taken into account by calculating the bounds of the drive torques with interval evaluation. When the desired next state is not valid for interference avoidance, a new state is scheduled by optimizing the next velocity, interval analysis is used again which allows to partition the complex constrained optimization problem into a simple two-stage problem. The resulting optimal state not only secures the robot against interference but also leads the robot to trace the desired path closely. Simulation results of a 2-DOF robot arm show the effectiveness of the proposed approach.